Quantum Chemical Calculations of 5-Diethylamino-2-{[4-(3-Methyl-3-Phenyl-Cyclobutyl)-Thiazol-2-yl]-Hydrazonomethyl}-Phenol Single Crystal Containing Heteroatoms - Karakurt, Tuncay; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Taylor & Francis Ltd, 2022)
5-Diethylamino-2-{[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazonomethyl}-phenol single crystal was synthesized and by using FT-IR, NMR and UV-Vis spectral techniques and X-ray diffraction method were characterized. It has adopted an enol-imine tautomeric form with a strong intramolecular O-H center dot center dot center dot N and intermolecular N-H center dot center dot center dot N hydrogen bond interaction. The compound has a photochromic property and is not planar. NMR chemical shift values, FT-IR and UV-Vis spectra of the title compound were theoretically calculated using density functional theory (DFT) and the spatial magnetic property known as visual ICSS employing the NICS concept was calculated. Using the TD-DFT method, the electronic absorption spectrum was calculated and determined to be in good agreement with the experimental UV-Vis values. It has been found that the title compound may have two tautomer structures (enol-imine and keto-amine). Tautomeric structures of the title compound were used to investigate corrosion inhibition effect on Cu and Fe metal atoms. Some quantum chemical parameters such as HOMO and LUMO orbital energies, electron affinity (IE), ionization potential (EA), electronegativity (chi), global hardness (eta) and global softness (S) were calculated. Using these parameters, the fraction of electrons (delta) transfer from inhibitor to metal was calculated to investigate the corrosion inhibition effects of Cu and Fe metals of the two tautomer structures. The corrosion inhibition effects of these structures were compared with the help of calculated quantum chemical parameters, and the relationships between quantum chemical parameters and the corrosion inhibition mechanism were analyzed. Electrophilic and nucleophilic attack sites of these tautomers also were examined using Fukui functions. In addition, optimized structure of the title compound in the solid phase was obtained using Quantum ESPRESSO under periodic boundary conditions (PBC).
Keywords: FT-IR; NMR and UV-Vis spectral techniques; X-ray; ICSS; corrosion inhibition; electrophilic and nucleophilic attack